2009
DOI: 10.1063/1.3073710
|View full text |Cite
|
Sign up to set email alerts
|

An optical spacer is no panacea for light collection in organic solar cells

Abstract: The role of an optical spacer layer has been examined by optical simulations of organic solar cells with various bandgaps. The simulations have been performed with the transfer matrix method and the finite element method. The results show that no beneficial effect can be expected by adding an optical spacer to a solar cell with an already optimized active layer thickness.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
43
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 78 publications
(44 citation statements)
references
References 20 publications
1
43
0
Order By: Relevance
“…[19,20] The need to quantify and develop a deep understanding of how to increase photocurrent by modifying device geometry is becoming increasingly important as materialcentric optimization strategies reach their limits and OPVs edge towards commercially relevant and significant efficiencies. [19][20][21][22][23][24] Herein, we report structuring of the organic-metal electrode interface in polymer-fullerene organic solar cells as a generic and facile approach towards attaining higher efficiencies and enabling the relative contributions to increased photocurrent to be elucidated. Analysis of the structure-induced changes in internal and external quantum efficiencies (IQEs and EQEs) shows that the increased photocurrent is derived both from enhanced optical trapping and improved electron extraction at the metal-active layer.…”
mentioning
confidence: 99%
“…[19,20] The need to quantify and develop a deep understanding of how to increase photocurrent by modifying device geometry is becoming increasingly important as materialcentric optimization strategies reach their limits and OPVs edge towards commercially relevant and significant efficiencies. [19][20][21][22][23][24] Herein, we report structuring of the organic-metal electrode interface in polymer-fullerene organic solar cells as a generic and facile approach towards attaining higher efficiencies and enabling the relative contributions to increased photocurrent to be elucidated. Analysis of the structure-induced changes in internal and external quantum efficiencies (IQEs and EQEs) shows that the increased photocurrent is derived both from enhanced optical trapping and improved electron extraction at the metal-active layer.…”
mentioning
confidence: 99%
“…Therefore, it has been suggested that the photocurrent can be increased by introducing an optical spacer that enhances light absorption in thin polymer solar cells by redistributing the optical electric field [4,5]. However, the spacer effect is only beneficial if the BHJ film thickness does not coincide with a local maximum of optical power dissipation [6].…”
Section: Introductionmentioning
confidence: 99%
“…The active layer of the most efficient polymer solar cells to date consists of a bulk heterojunction (BHJ) of a conjugated polymer with the buckminster fullerene derivative [6,6]-phenyl C 61 -butyric acid methyl ester (PCBM). Such a bulk heterojunction is characterized by nanoscale intermixing of the electron donor and acceptor materials in order to maximize their cross-sectional area [1].…”
Section: Introductionmentioning
confidence: 99%
“…Our results contribute to efforts to clarify and reconcile the role of optical spacers in organic solar cells. 12,15 We acknowledge Dr. Ebinazar Namdas of the University of Queensland, and Dr. Satish Patil of IISc Bangalore for providing the PTTDPP-BDT polymer. P.B.…”
mentioning
confidence: 99%
“…The trends observed in our experiments are helpful in reconciling the general debate on the effectiveness of optical spacers in organic solar cells, and also provide a systematic basis for optimising single junctions of complementary absorbers using interference effects. 12,15 In this study, we used the narrow optical gap polymeric donor poly (3,6-…”
mentioning
confidence: 99%